Evolution of NK cell receptors - Trowsdale, John (Henry Stewart Talks, 2009)
NK cells and receptors, Different species, Different receptors, Variation of NK receptors, Rapid evolution of NK receptors, Co-evolution of NK receptors and MHC class I, Implications